2012
DOI: 10.1098/rstb.2011.0222
|View full text |Cite
|
Sign up to set email alerts
|

Linking social complexity and vocal complexity: a parid perspective

Abstract: The Paridae family (chickadees, tits and titmice) is an interesting avian group in that species vary in important aspects of their social structure and many species have large and complex vocal repertoires. For this reason, parids represent an important set of species for testing the social complexity hypothesis for vocal communication—the notion that as groups increase in social complexity, there is a need for increased vocal complexity. Here, we describe the hypothesis and some of the early evidence that sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 99 publications
(110 citation statements)
references
References 135 publications
(159 reference statements)
3
99
1
Order By: Relevance
“…Birds face a variety of enemies such as predators (Caro 2005), nest predators (Martin 1993), and brood parasites (Rothstein 1990). In addition, many birds live in a complex social system that involves both cooperators and competitors from both conspecifics and heterospecifics, which might lead to complexity in their vocal systems (Krams et al 2012). Therefore, studying alarm-calling systems of wild birds would provide an ideal opportunity to investigate ways in which socio-ecological factors drive the evolution of sophisticated communication systems and their underlying cognitive processes.…”
Section: Discussionmentioning
confidence: 99%
“…Birds face a variety of enemies such as predators (Caro 2005), nest predators (Martin 1993), and brood parasites (Rothstein 1990). In addition, many birds live in a complex social system that involves both cooperators and competitors from both conspecifics and heterospecifics, which might lead to complexity in their vocal systems (Krams et al 2012). Therefore, studying alarm-calling systems of wild birds would provide an ideal opportunity to investigate ways in which socio-ecological factors drive the evolution of sophisticated communication systems and their underlying cognitive processes.…”
Section: Discussionmentioning
confidence: 99%
“…The dependent measure in the study was the amount of information in chick-a-dee calls of individuals. This call is the most common vocal signal used by individuals throughout the year and functions in social cohesion [69][70][71][72]. There seems to be a relationship between chick-a-dee call production and social affiliation in this species.…”
Section: A Brief Review Of the Evidence That Social Complexity Affectmentioning
confidence: 99%
“…We also tested titmice because they commonly use a complex calling system-the chick-a-dee call-that functions in social cohesion (Owens and Freeberg 2007;Sieving et al 2010). Studies have shown that calling rates and note composition of the titmouse chick-a-dee calls and related species change in the presence of a predator (Krams et al 2012). In this experiment, we manipulated the body and head orientation of a domestic cat model to face either toward or away from a food source.…”
Section: Introductionmentioning
confidence: 99%